Law Enforcement by Judge to Notary after Amendment of Notary Law - Suci Harumi; Amin Purnawan (Sultan Agung Notary Law Review, 2020)
Notary is a public official who is the only one authorized to make authentic deeds regarding all required agreements and decisions by General Regulations or by interested parties it is desired to be declared in an authentic deed, guarantees the certainty of the date, keeps the deed and provides the Grosse, copy and excerpt thereof, all so long as the deed is not assigned or excluded by an official or other person by a general rule. In Republic Indonesia Act No. 2 of 2014 concerning Amendments to Act No. 30 In 2004, for the photocopy of the minuta deed and notary summons there was no longer the role of the MPD and was replaced by the Notary Honorary Council. Then it becomes a question of how the Process for the emergence of the basis for the formation of the Notary Honorary Council in Act No. 2 of 2014 concerning Amendment Law on Notary Position Number 30 of 2004, and how the Notary Summons the Deed made by the Judge after the Amendment to the Notary Position Act No. 2 of 2014. Research is normative legal research, resulting in the conclusion that the Notary Honorary Council was born in the Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of Notary Public because of the need for protection of a Notary in making deeds. It is very necessary if there is an institution whose function is in the process of judicial interests, where the Notary must get permission from the Notary Honorary Council when summoned in a court session.